STUDI PERILAKU PEMILIH (VOTER BEHAVIOUR) PADA PEMILU LEGISLATIF (Studi Kasus Dapil 2 Kabupaten Muara Enim) - Markoni Markoni (Politeknik Negeri Sriwijaya, 2014)
The research is aimed to explore voter behaviour. This research is to identify factors that influence voters in determining their choice to candidates. It is merely case study whereas the research are mainly focus on legislative general election at constituency 5 in Muara Enim Regency. The research area sub-districs of Semendo, Tanjung Agung and Lawang Kidul. The main research problems to be explored are concerning with the important factors influence voters in determining their choice to legislator candidates. The research mainly used primary data by delivering questionaires to selected respondents. The questionaire was delivered to 660 selected respondents. It is also used secondary data to enrich the research analysis. Research finding shows that public figures, candidate’s personal characteristic , money potitics, ethnic, the son of soil are the main factors effected voters in choosing legislator candidates.